EOSINOPHILIC COLITIS MIMICKING CAECAL MALIGNANCY - Farooqi, Amer (Journal of Ayub Medical College Abbottabad, 2014)
Primary eosinophilic diseases of the gastrointestinal tract are increasingly being recognised in adults. Eosinophilic colitis is even less understood and presents with highly variable symptoms depending on the depth of mucosal involvement. We are presenting a case of primary eosinophilic colitis presenting with diarrhoea and localized caecal perforation. Pre-operative computed tomography suggested caecal malignancy and possible liver metastasis. Patient underwent an emergency laparoscopic right hemicoloectomy and histology revealed eosinophilic colitis. Post-operative period was complicated by pulmonary embolism and deep vein thrombosis. Secondary causes of eosinophilia were appropriately investigated and excluded. She made a good recovery and a post-operative colonoscopy looking for other areas of eosinophilia was normal. Keywords: Colitis, Eosinnophilic colitis, Budesonide, Caecal perforation